Pengaruh Electronic Word of Mouth terhadap Minat Beli yang di Mediasi oleh Brand Image pada Produk Lipstik Viva di Kota Cimahi - Fitriani, Indah; Herawati, Siti (Universitas Batanghari, 2024)
The aim of this research is to analyze the influence of electronic word of mouth on purchase intention mediated by brand image for Viva Lipstick products in Cimahi City. The number of samples used was 90 respondents with a purposive sampling technique which is included in nonprobability sampling. The data source in this research was obtained through distributing questionnaires that have been declared valid and reliable and have passed the classical assumption test. To carry out hypothesis testing in this research using simple regression tests, multiple regression tests, and Sobel tests. The tool used to carry out the test is using SPSS version 26 software. The results of the research show that electronic word of mouth has a positive and significant effect on brand image, electronic word of mouth has a positive and significant effect on purchase intention, brand image has a positive effect on purchase intention, and brand image plays a role in mediating the influence of electronic word of mouth on purchase intention.